Reversible Small Molecule Inhibitors of MAO A and MAO B with Anilide Motifs - Hagenow J; Hagenow S; Grau K; Khanfar M; Hefke L; Proschak E; Stark H (Dove Medical Press, 2020)
Jens Hagenow,1 Stefanie Hagenow,1 Kathrin Grau,1 Mohammad Khanfar,1– 3 Lena Hefke,4 Ewgenij Proschak,4 Holger Stark1 1Heinrich Heine University Düsseldorf, Institute of Pharmaceutical and Medicinal Chemistry, Duesseldorf 40225, Germany; 2Faculty of Pharmacy, The University of Jordan, Amman 11942, Jordan; 3College of Pharmacy, Alfaisal University, Riyadh 11533, Saudi Arabia; 4Goethe University Frankfurt, Institute of Pharmaceutical Chemistry, Frankfurt 60438, GermanyCorrespondence: Holger StarkHeinrich Heine University Duesseldorf, Institute of Pharmaceutical and Medicinal Chemistry, Universitaetsstr. 1, Duesseldorf 40225, GermanyTel +49 211 81-10478Fax +49 211 81-13359Email stark@hhu.deBackground: Ligands consisting of two aryl moieties connected via a short spacer were shown to be potent inhibitors of monoamine oxidases (MAO) A and B, which are known as suitable targets in treatment of neurological diseases. Based on this general blueprint, we synthesized a series of 66 small aromatic amide derivatives as novel MAO A/B inhibitors.Methods: The compounds were synthesized, purified and structurally confirmed by spectroscopic methods. Fluorimetric enzymological assays were performed to determine MAO A/B inhibition properties. Mode and reversibility of inhibition was determined for the most potent MAO B inhibitor. Docking poses and pharmacophore models were generated to confirm the in vitro results.Results: N-(2,4-Dinitrophenyl)benzo[d][1,3]dioxole-5-carboxamide ( 55, ST-2043) was found to be a reversible competitive moderately selective MAO B inhibitor (IC50 = 56 nM, Ki = 6.3 nM), while N-(2,4-dinitrophenyl)benzamide ( 7, ST-2023) showed higher preference for MAO A (IC50 = 126 nM). Computational analysis confirmed in vitro binding properties, where the anilides examined possessed high surface complementarity to MAO A/B active sites.Conclusion: The small molecule anilides with different substitution patterns were identified as potent MAO A/B inhibitors, which were active in nanomolar concentrations ranges. These small and easily accessible molecules are promising motifs, especially for newly designed multitargeted ligands taking advantage of these fragments.Keywords: salicylic acid derivatives, molecular modeling, Parkinson’s disease, enzyme inhibitor, pharmacophore, structure-activity relationships